Four-year outcomes of aflibercept treatment for neovascular age-related macular degeneration: Results from real-life setting. Issue 4 (July 2021) - Lukic, Marko; Eleftheriadou, Maria; Hamilton, Robin D; Rajendram, Ranjan; Bucan, Kajo; Patel, Praveen J
Background: To assess long-term structural and functional outcomes of intravitreal aflibercept (Eylea ® ) treatment for neovascular macular degeneration (nAMD) in a real-word setting. Design and methods: This was a retrospective, single-centre, non-randomized interventional cohort analysis. Data from treatment-naive patients with nAMD funded for treatment with intravitreal aflibercept in the period between 1 September 2013 and 28 February 2014 and who finished 4-year follow-up entered the analysis. Epidemiological data, visual acuity (VA) measured on ETDRS charts and injection numbers were recorded. Spectral domain optical coherence tomography (SD-OCT) data including presence or absence of macular fluid and automated central subfield macular thickness (CSMT) at year 1, 2, 3 and 4 were also recorded. Results: Ninety-four eyes of 89 patients finished 4-year follow-up. The mean number of aflibercept injections received over 4 years was 19.3. At baseline, the mean VA (SD) (Snellen) was 54.1 ± 15.5 (20/100) ETDRS letters whilst the mean CSM (SD) was 296 ± 81 µm. At 4 years, the mean VA (SD) (Snellen) was 60.4 ± 20.0 (20/63) ETDRS letters ( p  < 0.0001). Mean CSMT (SD) was 218 ± 79 μm ( p  < 0.0001). Thirty-three percent of eyes gained ⩾15 ETDRS letters at end of 4 years, and 66 (70%) eyes had no macular fluid at the end of the follow-up. Conclusion and relevance: The results suggest that good long-term morphological and functional treatment outcomes can be achieved using intravitreal aflibercept for nAMD in a real-life clinical setting.